Skin microbiota of children with acute urticaria of varying severity - Y. L. Naboka; A. A. Lebedenko; A. N. Posevina; L. A. Averkina; E. V. Ivannikova; E. V. Kudrya (Медицинский вестник Юга России, 2023)
Objective: to evaluate changes in the skin microbiota of the children with acute urticaria of varying severity. Materials and methods: a total of 94 children aged 3 to 14 years old were examined. Four clinical groups were formed. Group I (n=15) included children with mild acute urticaria, group II (n=32) – with moderate course, group III (n=16) – with severe form, and group IV (n=31) – children of the 1 and 2a health group (control group). All patients underwent a comprehensive clinical and laboratory examination, as well as a qualitative and quantitative assessment of the skin microbiota. The sampling of the material for bacteriological examination was carried out from the area of the middle third of the forearm on the affected area of the skin and on a symmetrical unaffected area in patients with acute urticaria. In the control group, the material was taken from the corresponding area of the forearm skin. Results: in the unaffected area of the skin in patients of group I, the rate of detection of Propionibacterium spp. (p<0.05) was increased, in group II, the rate of detection of Bacteroides spp. was increased (p<0.05), and in group III, the rate of detection of S. aigeis was increased and Micrococcus spp. (p<0.05) was reduced in comparison with the microbiota indicators of children in group IV. On the affected area of the skin in children of group II, the detection rate of Bacteroides spp. was significantly increased (p<0.05) and the detection rate of Bacillus spp. (p<0.05) was decreased, in children of group IV, the studied feature was increased for S. aureus (p<0.05). Conclusions: the data obtained during the study indicate differences in microbial patterns of the skin depending on the severity of the course of acute urticaria in children.